Micropropagation of cyclanthus bipartitus poiteau ex A. Richard and assessment of its genetic variability - Mohd Kasim, Nur Fauzana (2015)
Cyclanthus bipartitus is characterized as a rhizomatous, and terrestrial shrub with divided leaves and the plant can grow up to 460 cm in height. The plant can be propagated using seeds but seed set is very low, as the pollination process for this plant requires a specific pollinator. Even though this plant can be propagated by cutting and division, micropropagation seems to be the best method for commercial purposes as mass multiplication can be done at a faster rate compared to the conventional method. Thus, this study was carried out to develop an efficient protocol for micropropagation of C. bipartitus. More specifically, the objectives of the study were to determine suitable source of explants and to evaluate the effects of varying concentration of 6- benzylaminopurine (BAP) and 1-naphthaleneacetic acid (NAA) (as plant growth regulators), and concentration of sucrose (as a carbon source) for micropropagation of C. bipatitus. The study also aimed at determining the genetic variability of regenerated plants following micropropagation protocols adopted. Type of explants used in this study was first determined by excising 1 cm of explants from petiole and basal stem and 1 cm2 explants from distal and basal lamina, and culturing them in sterilized MS medium for containing BAP and NAA 10 weeks. Compared to other explants, distal lamina and basal lamina generated equally high number of shoots (with a mean of 49 shoots/explant). The shoot was also found to be significantly longer than those generated by other explant. Due to its superiority, explants from lamina part of the plant were used in the following experiments. An experiment to determine a suitable level of sucrose added to MS medium supplemented with BAP and NAA concentration was also performed. Explants were cultured in sterilized MS medium containing 1.0 mg/L of BAP and 0.5 mg/L NAA with five different concentrations of sucrose: 20 g/L, 25 g/L, 30 g/L,35 g/L and 40 g/L. The highest number of shoots/explant (54.88), tallest shoots (3.80 cm), highest number of roots (3.12) and longest root (0.78 cm) were obtained from explants cultured in MS media containing a combination of 1.0 mg/L of BAP, 0.5 mg/L of NAA and 30 g/L of sucrose after 10 weeks of culture. Genetic variability of regenerated plants at the DNA level was also analyzed by using random amplified polymorphic DNA (RAPD) molecular markers. Ten arbitrary primers were screened for RAPD use. Primers that produced scoreable bands were chosen to analyse polymorphism in regenerated plant DNA. By PCR amplification, 26 score-able bands were amplified from 5 primers out of 10 arbitrary primers screened, where 18 of them were polymorphic and 8 were monomorphic, which gave 69.2% of polymorphism frequency. In conclusion, explants from lamina part of the plant were used for propagating Cyclanthus bipartitus in vitro in MS medium supplemented with BAP and NAA concentrations of 1.0 mg/L and 0.5 mg/L, respectively. Regenerated plants from the micropropagation were shown to have 69.2% of polymorphism frequency, which indicates the occurrence of genetic variation subcultured plants.